From Multimedia Micro-University to Macro University and beyond. (February 2017) - Arndt, Timothy; Guercio, Angela
Abstract: For this special issue of the Journal of Visual Languages and Computing in honor of Prof. Shi-Kuo Chang we review Prof. Chang's research contributions to the field of education. Always visionary and inspirational, these works reflect Prof. Chang's student-centered approach and his interest in building relationships among international educators in order to bring the benefits of such collaborations among educators to the students while keeping in mind the motto "Small is beautiful".